1991
DOI: 10.1111/j.1834-7819.1991.tb00723.x
|View full text |Cite
|
Sign up to set email alerts
|

The oral health of the elderly in Melbourne

Abstract: A survey of 303 subjects over the age of 60 years collected demographic and oral health status data for analysis. The majority of the sample (64.2 per cent) were edentulous. Over 90 per cent of the dentate subjects required scaling and the removal of plaque (CPITN score of TN2); however, just less than half of the sextants examined were excluded because they contained fewer than two functional teeth. About one-third of the dentate subjects required no treatment for dental caries. Of those who required treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 4 publications
1
12
1
1
Order By: Relevance
“…Lower social status (Halling and Bengtsson, 1984;Bergman et al, 1991;Drake et al, 1995) and alcoholic beverage consumption (Kranzler et al, 1990;Drake et al, 1995) are associated with greater tooth loss. It is not known if caffeine intake has an independent effect on tooth loss.…”
Section: Introductionmentioning
confidence: 97%
“…Lower social status (Halling and Bengtsson, 1984;Bergman et al, 1991;Drake et al, 1995) and alcoholic beverage consumption (Kranzler et al, 1990;Drake et al, 1995) are associated with greater tooth loss. It is not known if caffeine intake has an independent effect on tooth loss.…”
Section: Introductionmentioning
confidence: 97%
“…Oral hygiene habits have been found to be poor among the elderly (Heloe, 1973;Richie, 1973;Grabowski &• Bertram, 1975;Langer, Michman & Librach, 1975). In their study of 303 subjects over the age of 60 years in Melbourne, Australia, Bergman, Wright & Hammond (1991) found that 91-96% of the dentate subjects required improvement in their oral hygiene habits.…”
Section: Introductionmentioning
confidence: 99%
“…Some special groups have been studied, for example nurs i n g home residents, 8 and older adults. [9][10][11] However, data specific to health card holders have been limited. Health card holders are the target group eligible for publicly-funded dental care.…”
Section: Introductionmentioning
confidence: 99%